Perampasan Aset Hasil Dari Kejahatan Money Laundering (Tinjauan Hukum Pidana Islam) - Al Qodri, Dhuha; Lubis, Syaddan Dintara (JURNAL LEGISIA, 2024)
This research examines the issues that hinder the process of money laundering and the seizure of assets resulting from money laundering in Indonesia. This study examines the issues that hinder the process of money laundering and the confiscation of assets resulting from money laundering crimes in Indonesia and the problems that arise when assets resulting from money laundering crimes are not easy to recover. This research uses normative legal research methods with literature data collection. The results showed that both Indonesian positive law and Islamic criminal law have provided legality to efforts to eradicate money laundering crimes. Asset forfeiture arrangements are outlined in Law No. 8/2010 on the Prevention and Eradication of Money Laundering Crimes under Indonesian positive law. A new law is needed to prevent and eradicate the crime of money laundering as the current laws have not been successful in stopping economic crime in Indonesia. Conversely, as the act is motivated by an attempt to legitimize the proceeds of crime, the forfeiture of assets arising from money laundering can be categorized as jarimah ta'zir in Islamic criminal law. In short, a thorough understanding of these two legal systems can enhance the effectiveness of initiatives aimed at combating money laundering.